Prostate Cancer: New Horizons in Research and Treatment - Cher, Michael L.; Raz, Avraham.; Honn, Kenneth V. (Developments in Oncology, 2002)
In recent years the pace of research in prostate cancer has increased dramatically. Creative ideas in combination with new and emerging technologies have led to an explosion of discovery. These types of advances in prostate cancer research presage an era of new treatment strategies based on an understanding of the cellular and molecular mechanisms of disease. In creating this book, we aimed to cover a broad "bench to bedside" research spectrum ranging from: genetic, molecular and cellular analyses to epidemiological studies, refinements in local treatment strategies and new biologically based non-hormonal treatments for systemic disease. Researchers and clinicians will find in this book a group of timely and clinically relevant chapters on prostate cancer research and treatment.